Endocytic SNAREs are involved in optimal Coxiella burnetii vacuole development - Campoy, Emanuel Martin (2013)
Coxiella burnetii is a Gram-negative intracellular bacterium. As previously described, both the endocytic and the autophagic pathways contribute to the maturation of Coxiella replicative vacuoles (CRVs). The large CRVs share the properties of both phagolysosomal and autophagolysosomal compartments. Vamp3, Vamp7 and Vamp8 are v-SNAREs involved in the endocytic pathway which participate mainly in the fusion between endosomes and lysosomes. In the present study we observed that Vamp7 interacts with C. burnetii at different infection times (1 h-48 h p.i.). We have determined that a truncated mutant of Vamp7 (Vamp7 NT) and a siRNA against this SNARE protein affects the optimal development of CRVs, suggesting that Vamp7 mediates fusion events that are required for the biogenesis of CRVs. Indeed, we have observed that overexpression of Vamp7 NT inhibited the heterotypic fusion with lysosomes and the homotypic fusion between individual Coxiella phagosomes and CRVs. Moreover, we have detected in the vacuole membrane, at different infection times, the Vamp7 partners (Vti1a and Vti1b). Interestingly, treatment with chloramphenicol reduced the colocalization between C. burnetii and Vamp7, Vti1a or Vti1b, indicating that the recruitment of these SNAREs proteins is a bacteria-driven process that favours the CRV biogenesis, likely by facilitating the interaction with the endolysosomal compartment